Unconventional valence metal compound composite material, preparation method and application

By self-assembling metal salts on graphene oxide films to form CuCl@rGO and CuO1-δ@rGO, the complex preparation problem was solved, and unconventional valence state metal compounds that are stable under atmospheric conditions were realized. These compounds exhibit high specific surface area and strong antibacterial activity, expanding their applications in catalysis, medicine, and electronic devices.

CN122035928APending Publication Date: 2026-05-15WENZHOU INST UNIV OF CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202512032784.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-05-15

AI Technical Summary

Technical Problem

Existing methods for preparing unconventional valence metal compounds are complex and demanding, limiting their applications in fields such as quantum criticality, superconductivity, strong antibacterial properties, and chemical catalysis.

Method used

Using multilayer reduced graphene oxide film as the main body, metal salts are embedded through self-assembly to form unconventional valence state metal compound composites, including CuCl@rGO and CuO1-δ@rGO, simplifying the preparation process and avoiding harsh conditions such as traditional high temperature and high pressure.

Benefits of technology

It exists stably under atmospheric conditions, possesses a high specific surface area and unique physical, chemical, and biological properties, and can be applied in chemical catalysis, biomedicine, and electronic devices to enhance reaction rates and antibacterial activity. It is also suitable for solar cells and gas molecule detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122035928A_ABST
    Figure CN122035928A_ABST
Patent Text Reader

Abstract

The invention relates to an unconventional valence metal compound composite material as well as a preparation method and application thereof, and solves the problems that the number of current unconventional valence systems is limited, the preparation method is relatively complicated, and protection conditions needing to be utilized for maintaining the unconventional valence are relatively harsh. The unconventional valence metal compound composite material is a composite functional material which takes a multi-layer reduced graphene oxide film as a main body and an unconventional valence compound which is self-filled into the reduced graphene oxide film as an object.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal compound technology, and more specifically, to an unconventional valence state metal compound composite material, its preparation method, and its application. Background Technology

[0002] Compounds with unconventional valence states are novel functional materials that can be applied in fields such as chemical catalysis and antibacterial medicine.

[0003] Scholars have developed an unconventional monovalent nickel-based material, whose monovalent Ni... + The orbital hybridization with O is weak, resulting in an infinitely layered Nd nickelate structure. 0.8 Sr 0.2 A novel superconducting phenomenon with a phase transition temperature of ~15K was discovered in NiO2 thin films. However, its synthesis method requires breaking through the traditional high-temperature solid-state method and adopting a low-temperature topological reduction synthesis method. Specifically, it relies on SrTiO3 as a substrate and uses pulsed laser deposition and CaH2 gas-phase reduction under two relatively harsh conditions.

[0004] A zero-magnetic-field intrinsic quantum critical phase, breaking the Fermi liquid theory, has been discovered in the intermetallic compound β-YbAlB4. Unlike traditional integer-valence Kondo lattice systems, Yb in β-YbAlB4 exhibits mixed valence states, and a unique competitive balance is achieved between valence fluctuations driven by ferromagnetic interactions and the Kondo shielding effect.

[0005] Two independent superconducting domes were found in the CeCu2Si2 superconductor, a similar lanthanide rare earth system. The superconducting mechanism of one of them is mediated by unconventional valence density fluctuations of Ce. The valence fluctuations of Ce require high pressure (~5.4 GPa) to induce local and itinerant quantum tunneling of 4f electrons.

[0006] Cu, an element with numerous applications, most commonly exists in a +2 valence state. However, the +1 valence cuprous ion is unstable under atmospheric conditions. For example, CuCl undergoes a disproportionation reaction in air to become zero-valent copper and +2 valence CuCl2, while Cu2O gradually oxidizes to +2 valence CuO in the atmosphere. Studies have found that +1 valence Cu... + It possesses a variety of excellent properties. Magal Saphie, through studies on the antibacterial effects against Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus), confirmed the effectiveness of uncommon Cu. + Compared to Cu 2+ It exhibits more significant antibacterial activity, and its effect is even superior to that of silver ions (Ag) commonly used in clinical practice. + Monovalent copper is produced by the reaction of elemental copper or ascorbic acid with Cu. 2+The reduction of Cu was achieved under strictly anaerobic conditions, including high-purity argon gas bubbling deoxygenation and complete oxygen isolation in a sealed environment. + Cu plays a crucial role in the electrochemical reduction of CO2 by Cu-based catalysts. The Cu surface undergoes structural evolution through a "dissolution-redeposition" process, producing intermediate transition states mediated by adsorbate complexes, with monovalent Cu being a key component. + It exists only momentarily in solution and requires targeting active Cu. + Measures such as organic layer protection, electric field pulses, and porous carbon confinement are used to enhance the positive valence of Cu. + Lifespan.

[0007] Existing technology has developed a high-performance photocathode with a monovalent cuprous oxide (Cu₂O) nanowire structure, achieving efficient and stable solar water splitting with an experimental solar-to-hydrogen conversion efficiency of approximately 3%. Maintaining the catalytic core Cu₂O is achieved by depositing a TiO₂ chemical corrosion protection layer on the outer layer of Cu₂O using atomic layer deposition (ALD) technology.

[0008] Existing technology includes a CuCl / Y material of monovalent copper prepared from divalent CuCl2 using a monolayer dispersion reduction method with Y-based molecular sieves. This material can be used for the efficient and selective separation of CO gas. The monovalent Cu... + Its stable existence is due to the strictly inert atmosphere of the reaction: Cu + Separation experiments were conducted only on non-oxidizing and water vapor-free CO2, CH4, and N2.

[0009] However, the number of unconventional valence systems is currently limited, and the protective conditions required to maintain this uncommon valence are quite stringent, and the preparation methods are relatively complex, which greatly limits the application of this series of compounds (such as practical applications in fields such as quantum criticality, superconductivity, strong antibacterial properties, and chemical catalysis). Summary of the Invention

[0010] This application aims to solve the above-mentioned technical problems by providing an unconventional valence state metal compound composite material, its preparation method, and its application.

[0011] Unconventional valence state metal compound composites are functional materials with multilayer reduced graphene oxide films as the main body and unconventional valence state compounds that are self-filled into the reduced graphene oxide films as the guest.

[0012] The first aspect of this disclosure provides a method for preparing unconventional valence state metal compound composite materials, comprising the following steps:

[0013] Step S1: A certain amount of graphene oxide is dropped onto hydrophobic silicone paper to form graphene oxide droplets;

[0014] Step S2: Place the hydrophobic silicone paper with attached graphene oxide droplets in an oven and dry it to form a multilayer graphene oxide film.

[0015] Step S3: Remove the graphene oxide film from the oven and repeatedly soak it in deionized water to dissolve and remove metal ion impurities.

[0016] Step S4: Place the graphene oxide film treated in step S3 into an oven for drying.

[0017] Step S5: Immerse the graphene oxide film after drying in step S4 into a metal salt aqueous solution to allow the graphene oxide film to adsorb the metal salt.

[0018] Step S6: Place the graphene oxide membrane with adsorbed metal salts into a centrifuge and centrifuge at high speed to remove excess metal salt solution.

[0019] Step S7: Place the graphene oxide film with adsorbed metal salts after step S6 into an oven for drying.

[0020] Step S8: The graphene oxide film with adsorbed metal salts after drying in step S7 is placed in a muffle furnace and slowly heated to a certain temperature, and then left to stand to obtain the final product, an unconventional valence metal compound.

[0021] Preferably, the metal element in the aqueous solution of the metal salt is any one of Li, Na, K, Mg, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, and Al.

[0022] Preferably, in step S5, the concentration of the metal salt is 1M.

[0023] Preferably, the metal salt aqueous solution is a CuCl2 aqueous solution; in step S8, CuCl2 in the multilayer structure of graphene oxide forms a self-assembled structure, reducing graphene oxide to reduced graphene oxide, and obtaining the final product composite material CuCl@rGO.

[0024] Preferably, the metal salt aqueous solution is a Cu(NO3)2 aqueous solution. In step S8, the Cu(NO3)2 in the multilayer structure of graphene oxide decomposes into copper oxide, reducing the graphene oxide to reduced graphene oxide, thus obtaining the final product composite material CuO. 1-δ @rGO.

[0025] A second aspect of this disclosure provides an unconventional valence state metal compound composite material prepared by any of the above preparation methods.

[0026] A third aspect of this disclosure provides the application of the above-obtained unconventional valence state metal compound composite material in chemical catalysis, biomedical antibacterial, or gas molecule detection electronic devices.

[0027] A fourth aspect of this disclosure provides an unconventional valence state metal compound composite material, the structural expression of which is: CuCl@rGO.

[0028] The fifth aspect of this disclosure provides an unconventional valence state metal compound composite material, the structural expression of which is: CuO 1-δ @rGO.

[0029] The technical solution disclosed in this application departs from the following methods: traditional pulsed laser-assisted strong reducing agent, unique competitive balance between valence state fluctuation ferromagnetic interaction and Kondo shielding effect, high voltage-induced local and itinerant quantum tunneling of electrons, high-purity argon deoxygenation and strict isolation of oxygen throughout the process, continuous reduction with excessive ascorbic acid, and complex measures such as atomic layer deposition of TiO2 chemical corrosion protective layer.

[0030] The beneficial effects of this disclosure are that unconventional valence state metal compound composite materials can exist stably for a long time under atmospheric conditions, do not require harsh maintenance conditions, have high specific surface area characteristics, and have a simple preparation method.

[0031] Unconventional valence metal compounds are characterized by a group of compounds with unusual valence states, in which the metal ions exhibit atypical valence behaviors that deviate from standard chemical behavior. These often lead to unusual physical, chemical, and biological properties, and have applications in various fields such as physical, chemical, and biomaterials engineering.

[0032] In the field of chemical catalysis, unconventional copper can be used to activate carbon-carbon and carbon-heteroatom reactions, increasing reaction rates by millions of times. It features low cost, few side reactions, and high selectivity for target molecules. In the biomedical field, monovalent copper has high biocompatibility and excellent antibacterial activity. Trace amounts of copper compounds can rapidly and efficiently kill norovirus, Staphylococcus aureus, Escherichia coli, etc., exhibiting strong broad-spectrum antibacterial activity against bacteria, viruses, and fungi. In the field of electronic devices, unconventional copper compounds have band energy matching that of visible natural light, making them suitable for photovoltaic power generation in solar cells. Unconventional copper-based nanomaterials have excellent surface conductivity and specific adsorption properties, making them suitable for high-sensitivity detection and sensing of gas molecules such as H2S and NO2.

[0033] Further features and aspects of the present invention will be clearly described in the following detailed description with reference to the accompanying drawings. Attached Figure Description

[0034] Figure 1 This is a scanning electron microscope image of CuCl@rGO, showing the composite material.

[0035] Figure 2 Scanning electron microscopy was used to examine the composite material, revealing CuO. 1-δ @rGO's photo;

[0036] Figure 3 Transmission electron microscopy (TEM) analysis of the composite material revealed CuO. 1-δ @rGO's photo;

[0037] Figure 4 The X-ray diffraction pattern for CuCl@rGO is obtained by X-ray diffraction testing of the composite material.

[0038] Figure 5 X-ray diffraction testing of composite materials yielded results targeting CuO. 1-δ X-ray diffraction pattern of @rGO;

[0039] Figure 6 The composite material was subjected to X-ray photoelectron spectroscopy to obtain the XPS spectrum for CuCl@rGO;

[0040] Figure 7 X-ray photoelectron spectroscopy (XPS) is used to detect composite materials to obtain specific targets for CuO. 1-δ @rGO's XPS spectrum;

[0041] Figure 8 Raman spectroscopy was performed on the composite material to obtain the target CuO 1-δ @rGO's spectrum;

[0042] Figure 9 The magnetic curves for CuCl@rGO were obtained by performing magnetic MPMS measurements on the composite material.

[0043] Figure 10 The magnetic MPMS measurement of the composite material was performed to obtain the specific properties of CuO. 1-δ @rGO's magnetic curve;

[0044] Figure 11 The specific surface area is obtained by measuring the specific surface area of ​​the CuCl@rGO composite material.

[0045] Figure 12 For composite materials CuO 1-δ @rGO performs specific surface area detection and obtains the specific surface area value;

[0046] Figure 13 This is a photograph taken using a scanning electron microscope to examine reduced graphene oxide. Detailed Implementation

[0047] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0048] The specific embodiments described below are merely preferred embodiments of this application, and the scope of protection of this application is not limited thereto. Those skilled in the art can make modifications or variations based on the principles, concepts, and spirit of this application, and the resulting technical solutions should all be covered within the scope of protection of this application.

[0049] The following uses Cu as an example to illustrate a specific implementation scheme. The preparation method is as follows:

[0050] Example 1

[0051] Step S1: 1 mL of graphene oxide (GO) is dropped onto hydrophobic silicone paper in the form of a circular droplet, thus forming a graphene oxide droplet.

[0052] Step S2: Place the hydrophobic silicone paper with attached graphene oxide droplets in an oven and dry it at 70°C for 12 hours to form a multilayer graphene oxide film.

[0053] Step S3: Remove the graphene oxide film from the oven and repeatedly soak it in deionized water to dissolve and remove various adsorbed metal ion impurities.

[0054] Step S4: Place the cleaned graphene oxide film into an oven and dry it at 70°C for 12 hours to perform a reshaping process.

[0055] Step S5: Immerse the graphene oxide film after drying in step S4 into a 1M CuCl2 aqueous solution to fully soak it, so that the Cu salt is embedded in the gaps of the graphene oxide film.

[0056] Step S6: Place the graphene oxide membrane with adsorbed Cu metal salt into a centrifuge and centrifuge at 10,000 rpm for 1 hour to remove excess Cu metal salt solution.

[0057] Step S7: Place the graphene oxide film with adsorbed Cu metal salt after step S6 into an oven and dry it at 70°C for 12 hours.

[0058] In step S8, the graphene oxide film adsorbed with Cu metal salt, after drying in step S7, is placed in a muffle furnace and slowly heated to 190°C and allowed to stand for 3 days. This allows CuCl2 in the multilayer structure of the graphene oxide to form a self-assembled structure, reducing the graphene oxide to reduced graphene oxide (rGO). With the reduced graphene oxide film as the host and cuprous chloride as the guest, the final product, the host-guest composite material CuCl@rGO, is obtained.

[0059] Images obtained using scanning electron microscopy only for reduced graphene oxide, such as... Figure 13 As shown, it exhibits a multi-layered structure, with metal compounds filling the spaces between the layers.

[0060] Step S9: The CuCl@rGO composite material was stored under atmospheric conditions for 30 days, and then subjected to various tests including scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, magnetic measurements (MPMS), and specific surface area (BET). Figure 1 Scanning electron microscopy revealed that CuCl was embedded and attached to the surface of the reduced graphene oxide layer, with CuCl crystals ranging in size from 50 to 200 nm. Figure 4 The X-ray diffraction pattern shows that the characteristic peaks for CuCl@rGO match those of CuCl salt. From... Figure 6 The XPS spectra show that Cu exhibits a +1 valence in CuCl@rGO. From... Figure 9 As can be seen, the MPMS 2K magnetic test on CuCl@rGO shows an unusually strong paramagnetic property. From... Figure 11 The BET test results show that CuCl@rGO exhibits a high specific surface area of ​​41.6 m². 2 / g.

[0061] The preparation method is simple and inexpensive. The host-guest composite material CuCl@rGO can remain stable under atmospheric conditions for a long time.

[0062] The host-guest composite CuCl@rGO contains a group of compounds with unusual valence states, in which metal ions exhibit valence behaviors that are difficult to sustain stably under normal conditions. These valence states often induce unusual physical, chemical, and biological properties.

[0063] This invention utilizes simple experimental conditions to obtain unconventional valence metal ion compounds that are stable under atmospheric conditions and exhibit unusually strong superparamagnetic properties. The materials also possess high specific surface area and open unconventional valence compound interfaces. These materials show broad application prospects in many fields such as biomedicine, chemical catalysis, and electronic devices.

[0064] Example 2

[0065] Step S1: 1 mL of graphene oxide (GO) is dropped onto hydrophobic silicone paper in the form of a circular droplet, thus forming a graphene oxide droplet.

[0066] Step S2: Place the hydrophobic silicone paper with attached graphene oxide droplets in an oven and dry it at 70°C for 12 hours to form a multilayer graphene oxide film.

[0067] Step S3: Remove the graphene oxide film from the oven and repeatedly soak it in deionized water to dissolve and remove various adsorbed metal ion impurities.

[0068] Step S4: Place the cleaned graphene oxide film into an oven and dry it at 70°C for 12 hours to perform a reshaping process.

[0069] Step S5: Immerse the graphene oxide film dried in step S4 into a 1MC Cu(NO3)2 aqueous solution for a thorough soaking, so that the Cu salt is embedded in the gaps of the graphene oxide film.

[0070] Step S6: Place the graphene oxide membrane with adsorbed Cu metal salt into a centrifuge and centrifuge at 10,000 rpm for 1 hour to remove excess Cu metal salt solution.

[0071] Step S7: Place the graphene oxide film with adsorbed Cu metal salt after step S6 into an oven and dry it at 70°C for 12 hours.

[0072] Step S8: The graphene oxide film adsorbed with Cu metal salt, after drying in step S7, is placed in a muffle furnace and slowly heated to 190°C and allowed to stand for 3 days. This allows Cu(NO3)2 in the multilayer structure of graphene oxide to decompose into copper oxide, reducing the graphene oxide to reduced graphene oxide (rGO). The reduced graphene oxide film serves as the host, and the copper oxide as the guest, yielding the final product, a host-guest composite material CuO. 1-δ @rGO.

[0073] Step S9, the composite material CuO 1-δ @rGO was stored under atmospheric conditions for 30 days, and then subjected to various tests including scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, magnetic measurements (MPMS), and specific surface area (BET). Figure 2 Scanning electron microscope, Figure 3 Transmission electron microscopy reveals that CuO 1-δ Embedded and attached to the surface of the reduced graphene oxide layer, CuO 1-δ The crystal size distribution ranges from 10 to 150 nm. Figure 5 The X-ray diffraction pattern shows that, regarding CuO 1-δ @rGO, the characteristic peaks basically match those of CuO, with a slight shift in peak position. From Figure 7 The XPS spectra show that, regarding CuO 1-δ @rGO, Cu has a non-standard +2 valence, exhibiting a transitional state shifting from +2 to +1 valence. From Figure 8 The Raman spectrum shows that, regarding CuO1-δ @rGO, Cu's 282cm -1 The characteristic peaks show a shift in oxidation state from +2 to +1. Figure 10 It can be seen that, regarding CuO 1-δ @rGO, MPMS2K magnetic testing shows unusually strong paramagnetism. From Figure 12 The BET test results show that, regarding CuO 1-δ @rGO exhibits a high specific surface area of ​​10.4m². 2 / g.

[0074] The preparation method is simple and inexpensive. The host-guest composite material is CuO. 1-δ @rGO can exist stably for a long time under atmospheric conditions.

[0075] Host-guest composite material CuO 1-δ @rGO comprises a group of compounds with unusual valence states, in which metal ions exhibit atypical valence behaviors that deviate from standard chemical behavior. These often result in unusual physical, chemical, and biological properties.

[0076] This invention utilizes simple experimental conditions to obtain unconventional valence metal ion compounds that are stable under atmospheric conditions and exhibit unusually strong superparamagnetic properties. The materials also possess high specific surface area and open unconventional valence compound interfaces. These materials show broad application prospects in many fields such as biomedicine, chemical catalysis, and electronic devices.

[0077] In the preparation method, the Cu element prepared in the early stage exists in the form of soluble metal salts, such as halides, acetates, carbonates, sulfates, phosphates, or nitrates.

[0078] The above composite materials CuCl@rGO and CuO 1-δ @rGO uses Cu as an example, but it can also be other metallic elements, such as Li, Na, K, Mg, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Cd, or Al. Metal salts can also be composed of other anions, such as halides, acetates, carbonates, sulfates, or phosphates.

Claims

1. A method for preparing an unconventional valence state metal compound composite material, characterized in that, Includes the following steps: Step S1: A certain amount of graphene oxide is dropped onto hydrophobic silicone paper to form graphene oxide droplets; Step S2: Place the hydrophobic silicone paper with attached graphene oxide droplets in an oven and dry it to form a multilayer graphene oxide film. Step S3: Remove the graphene oxide film from the oven and repeatedly soak it in deionized water to dissolve and remove metal ion impurities. Step S4: Place the graphene oxide film treated in step S3 into an oven for drying. Step S5: Immerse the graphene oxide film after drying in step S4 into a metal salt aqueous solution to allow the graphene oxide film to adsorb the metal salt. Step S6: Place the graphene oxide membrane with adsorbed metal salts into a centrifuge and centrifuge at high speed to remove excess metal salt solution. Step S7: Place the graphene oxide film with adsorbed metal salts after step S6 into an oven for drying. Step S8: The graphene oxide film with adsorbed metal salts after drying in step S7 is placed in a muffle furnace and slowly heated to a certain temperature, and then left to stand to obtain the final product, an unconventional valence metal compound.

2. The method for preparing unconventional valence state metal compound composite materials according to claim 1, characterized in that, The metal element in the aqueous solution of the metal salt is any one of Li, Na, K, Mg, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Cd, and Al.

3. The method for preparing unconventional valence state metal compound composite materials according to claim 1, characterized in that, In step S5, the concentration of the metal salt is 1M.

4. The method for preparing unconventional valence state metal compound composite materials according to claim 2, characterized in that, The metal salt aqueous solution is a CuCl2 aqueous solution; in step S8, CuCl2 in the multilayer structure of graphene oxide forms a self-assembled structure, reducing graphene oxide to reduced graphene oxide, and obtaining the final product composite material CuCl@rGO.

5. The method for preparing unconventional valence state metal compound composite materials according to claim 2, characterized in that, The metal salt aqueous solution is a Cu(NO3)2 aqueous solution. In step S8, the Cu(NO3)2 in the multilayer structure of graphene oxide decomposes into copper oxide, reducing the graphene oxide to reduced graphene oxide, and obtaining the final product composite material CuO. 1-δ @rGO.

6. The unconventional valence state metal compound composite material prepared by the preparation method according to any one of claims 1-5.

7. The application of the unconventional valence state metal compound composite material of claim 6 in chemical catalysis, biomedical antibacterial or gas molecule detection electronic devices.

8. A composite material of unconventional valence state metal compounds, characterized in that, The structural expression of the unconventional valence state metal compound composite material is: CuCl@rGO.

9. A composite material of unconventional valence state metal compounds, characterized in that, The structural expression of the unconventional valence state metal compound composite material is: CuO 1-δ @rGO.